1957
DOI: 10.2134/agronj1957.00021962004900010005x
|View full text |Cite
|
Sign up to set email alerts
|

Root Development of Winter Wheat as Influenced by Soil Moisture and Nitrogen Fertilization1

Abstract: Synopsis Root development of winter wheat was studied in central Nebraska. Depth of soil moisture and rate of nitrogen fertilization were variables. A dense network of roots developed in soil when soil moisture tension was above 15 atmospheres. When moisture conditions were favorable, roots were observed at a depth of 13 feet. There was evidence of moisture depletion to a depth of 8 feet. Nitrogen fertilization increased root weights and moisture utilization at all moisture levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 3 publications
2
49
0
Order By: Relevance
“…Furthermore, N uptake in tillers increases when N fertiliser is applied (Power & Alessi 1978) and root systems are also reportedly larger (Kmoch et al 1957). As a result, it seems that during stem extension, N increases the ability of a tiller to compete with the main stem sinks for assimilate or to produce more of its own assimilate and retain it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, N uptake in tillers increases when N fertiliser is applied (Power & Alessi 1978) and root systems are also reportedly larger (Kmoch et al 1957). As a result, it seems that during stem extension, N increases the ability of a tiller to compete with the main stem sinks for assimilate or to produce more of its own assimilate and retain it.…”
Section: Discussionmentioning
confidence: 99%
“…Root competition for nutrients between tillers is another factor that could restrict tillering at high seeding rates. This aspect needs to be explored further as root growth is dependent on carbohydrate supply for shoots (Welbank et al 1973), as well as N nutrition (Kmoch et al 1957). …”
Section: Discussionmentioning
confidence: 99%
“…The major part of the wheat roots develops in the top 20 cm soil layer (Barraclough and Leigh 1984), but some roots can reach the 100cm layer and deeper (Kmoch et al 1957;Hamblin and Tennant 1987). To obtain the complete root system, soil sampling from deeper layers is also necessary.…”
Section: S=(m)(cv)/lo0mentioning
confidence: 99%
“…Efficiency of moisture use as measured by grain production was increased manyfold by application of fertilizer. Good N nutrition increased subsequent moisture utilization during a critical period of plant development prior to and during tassel ing (Linscott et_ aJ., 1962), but materially reduced the amount of water required to produce a bushel of com (Smith, 1954;Kmoch et al, 1957;and Musick et al (1963) concluded that applied N increased seasonal évapotranspiration under conditions of appreciable response. Increased yields of com were disproportionately greater than the slight increase in évapotranspiration.…”
Section: Effects and Efficiencymentioning
confidence: 99%
“…Besides, N-fertilized corn develops a deeper and more extensive root system during the early part of the growing season than does un-fertilized corn (Kmoch et al, 1957;Linscott et al, 1962;Jordan et al, 1958). Thus, for the greatest response to N, higher moisture than the mean ASM would be preferable in the early periods and …”
Section: Distributional Effect Of Available Soil Moisturementioning
confidence: 99%